Strategic Action Plan (SAP) UiTMCP 2024: Globally Respected University UiTMCP Towards Sustainable Smart Campus 2025/ NoorAileen Ibrahim and Nuramira Anuar - Ibrahim, NoorAileen; Anuar, Nuramira (2024)
On the 31st of January 2024, the Academy of Language Studies of UiTM Perak Branch or Akademi Pengajian Bahasa (APB) organized a Strategic Planning Workshop held at Bilik ILQAM and had invited the honourable Rector Associate Professor Dr. Nur Hisham Ibrahim (PMP) to present a talk during the first session entitled ‘‘Strategic Action Plan (SAP) UiTMCP 2024: Globally Respected University. UiTMCP Towards Sustainable Smart Campus 2025’. This Strategic Planning workshop was divided into five sessions and the participants were APB lecturers from UiTM Seri Iskandar and Tapah.